1980
DOI: 10.1007/bf01965981
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that endogenous vasopressin plays a protective role in circulatory shock. Role for reticuloendothelial system using Brattleboro rats

Abstract: Experiments performed on male Wistar, Long Evans and Brattleboro rats indicate that the latter strain of animals, lacking vasopressin in their posterior pituitaries, are extremely sensitive to hemorrhagic and bowel ischemic shock. Mild forms of both hemorrhagic and bowel ischemic shock, as produced in Wistar or Long Evans rats, results in marked hypotension, hemoconcentration and blockade of the reticuloendothelial system (RES) in Brattleboro animals of similar sex, age and weight. These direct findings indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
(1 reference statement)
0
5
0
3
Order By: Relevance
“…rats which also showed that these animals are much more susceptible to blood loss than l.e. rats (Altura, 1980). Altura suggested that the absence of the constrictor effect of the hormone on the microcirculation in b.d.i.…”
Section: Resultsmentioning
confidence: 99%
“…rats which also showed that these animals are much more susceptible to blood loss than l.e. rats (Altura, 1980). Altura suggested that the absence of the constrictor effect of the hormone on the microcirculation in b.d.i.…”
Section: Resultsmentioning
confidence: 99%
“…Arginine vasopressin could exert a positive influence on the water balance system (195), the cardiovascular system (196), the immune system (197)(198)(199)(200), the adrenal system (20 1,202), and the respiratory system (203,204). Now, as a result of these exhaustive studies, it is clear that this neurohormone acts centrally on the thermoregulatory system in a manner which may be quite beneficial to the animal during a febrile episode.…”
Section: Avp: Its Role As An Endogenous Antipyreticmentioning
confidence: 99%
“…Таким образом, хотя выявленное повышение уровня ВП у пациентов с ХСН в сравнении со здоровыми представителями контрольной группы в целом соответствовало данным литературы [10,15,16], установленное нами относительное снижение уровня ВП у пациентов с ХСН III стадии и IV ФК ранее мало описано в литературе. Так, по данным S. Masson и соавт., уровень копептина (является С-концевой частью прогормона ВП, производимой организмом в эквимолярном ВП количестве) в группе пациентов с III и IV ФК ХСН статистически значимо выше, чем в группе пациентов со II ФК [17].…”
Section: Discussionunclassified
“…С одной стороны, изменение О р и г и н а л ь н ы е и с с л е д о в а н и я уровня ВП у пациентов с ростом тяжести ХСН может иметь двоякий характер. Так, на начальной и клинически выраженной стадии ХСН повышение уровня ВП играет негативную роль, стимулируя задержку жидкости и прогрессирование сердечной недостаточности [9,10]; однако на последних стадиях оно может сменяться истощением нейронов гипоталамуса и относительным дефицитом ВП, который может как являться одной из причин негативного прогноза у таких пациентов, так и быть лишь одним из симптомов истощения организма и нарушения регуляции гипоталамо-гипофизарно-надпочечниковой оси у пациентов с терминальной и декомпенсированной ХСН [20].…”
Section: Discussionunclassified
See 1 more Smart Citation